Pendidikan Islam Sebagai Way of Life; Refleksi Pencarian Spektrum Generasi Profetik - Abd. Basid (At- Ta'lim : Jurnal Pendidikan, 2019)
Islam with its teachings from the Qur’an and the Hadith which are enriched by interpreters and takwil of the ulamas has shown clearly and highly to various problems found in education. Therefore we do not say wrongly that epistemologically, Islam has a unique concept of education, namely Islamic education. Islamic education as rational and empirical knowledge of Islamic education, outlines educational theory that can be applied in the activities of the teaching and learning process. Islamic teaching views humans as body, mind and heart. The view of Islam is different from the west who sees humans as mere bodies and minds. The logical consequence of this view is that the curriculum, methods and other components do not pay attention to just one aspect. Physical, reason and conscience have the same place in Islamic education. And only as Islamic teachings have guided humans to become whole human beings, including also about how the concept and orientation of education in Islam. Keywords: Islamic education as a way of life